Generation and Release of OH Radicals from the Reaction of H2O with O2 over Soot. (24th March 2022) - He, Guangzhi; Ma, Jinzhu; Chu, Biwu; Hu, Renzhi; Li, Hao; Gao, Meng; Liu, Yuan; Wang, Yonghong; Ma, Qingxin; Xie, Pinhua; Zhang, Guoxian; Zeng, Xiao Cheng; et al.
Abstract: OH radicals in the air maintain the oxidizing power of the troposphere. A conventional view is that particulate matter (PM) in the atmosphere is a major sink of OH radicals, thereby lowering the oxidizing power of atmosphere in the event of high‐level PM. By contrary, our joint experimental/theoretical study reveals a new mechanism for the generation of gaseous OH radicals by carbonaceous soot particles. We show that water and O2 react on carbonaceous surfaces and give rise to gaseous OH radicals under irradiation. With ample delocalized π electrons, carbonaceous surfaces enable the easy desorption of hydroxyl groups to produce gaseous OH radicals, evidenced by direct observation of the steady generation of OH radicals on a carbonaceous surface. Our results reveal a new chemical mechanism for the production of OH radicals. Abstract : A new chemical mechanism for the generation of gaseous OH radicals by the reaction of H2 O with O2 over soot was revealed, which indicates the airborne soot particles generated by the incomplete combustion of hydrocarbons may entail important catalytic oxidation capacity.